English for Specific Purposes: Needs Analysis of EFL Learning Activites for Physical Education Students - Putra, Aziiz Rahman; Pradana, Ami; Banat, Azizatul; Dewa, Barata Harsena (Journal of Language Intelligence and Culture, 2025)
This study examines the English language needs of Physical Education EFL students at Dehasen University, Indonesia, using the English for Specific Purposes (ESP) approach. It fills a gap in ESP research about the specific needs of Physical Education students in Indonesia. A mixed-methods design was used, collecting data from 42 students via questionnaires and from interviews with one English lecturer and one Physical Education lecturer. Data were analyzed using descriptive statistics and thematic coding. Results show that 95% of students consider English important, especially speaking (76%) and listening (10%) skills for communication in academic practicum settings. The main challenges reported were listening (40%) and speaking (30%), while writing was the lowest priority. Most students are motivated to learn English for work (55%) and communication (31%). Lecturers agree on teaching integrated skills but emphasize oral communication and pronunciation. The findings suggest ESP curricula should focus on sports-related vocabulary and practical communication tasks. Diverse teaching methods are recommended to improve student engagement and language learning. This study offers practical recommendations for syllabus design that meet the academic and professional needs of Physical Education students, emphasizing communicative competence—especially speaking and listening—to prepare them for future careers.